A study on variation of maximum temperature over Bhopal during last decade - BALAKRISHNAN, TK; DUBEY , DP (MAUSAM, 1989)
Daily maximum temperatures of Bhopal for four summer months, i.e., March. June have been studied for the years 1977 to 1987. From daily values of maximum temperatures, changes from the previous day value were calculated. Daily departures were also calculated. Depending upon their ranges, the changes are classified as per the standard meteorological convention. The frequency of occurrence of each category has been worked out for these months. Similar anaysis has been done for departures also. Percentage number of cases in the month where the temperature either continuously falls, rises or does not change for more than one day have been documented separately. Results indicate that in case of changes, ’Little change’ together with ’No change’ pre-dominates and accounts for 65% of the cases. It is observed that for all the months there is a gradual fall in the percentage frequency as the magnitude of variation of maximum temperature increases.